Social entrepreneurship and the motivations for social enterprise creation - Martinez Garza, Alejandra (2016)
Social entrepreneurship and social enterprises have been the subject of study in the past few years. The entrepreneurs behind the management of these types of social ventures are known as social entrepreneurs. The purpose of this dissertation is to investigate social entrepreneurship, social entrepreneurs and social enterprises, through addressing the following research question: “What are the motivations that often lead social entrepreneurs to start social enterprises?” Starting from this question, the study also covers the understanding that social entrepreneurs have about social firms and their intentions, and addresses the challenges entrepreneurs have faced throughout the process of creating their social start-ups. Semi-structured interviews were the selected research method for data collection. Interviews were administered to seven British social entrepreneurs who currently own international, national or local social start-ups. Thematic analysis was used throughout the research, with the following emerged themes: motivations of social entrepreneurs, understanding of social enterprises by social entrepreneurs and challenges social entrepreneurs have faced. The findings from this research illustrate that each social entrepreneur has different motivations for starting their social enterprise; these are malleable and affected by their backgrounds, experiences and surroundings; and entrepreneurs tend to have difficulty balancing both economic and social objectives of their business. Other findings show the challenges these social entrepreneurs have faced – in obtaining funding to start and expand their social venture; having the proper business knowledge to manage their start-up; and obtaining the support needed from their inner circle to overcome the evolving challenges they faced. A more in-depth analysis of the results, implications, limitations and contributions is discussed in this dissertation.